Intelligent Computing Proceedings of the 2018 Computing Conference, Volume 2 - Arai, Kohei; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book, gathering the Proceedings of the 2018 Computing Conference, offers a remarkable collection of chapters covering a wide range of topics in intelligent systems, computing and their real-world applications. The Conference attracted a total of 568 submissions from pioneering researchers, scientists, industrial engineers, and students from all around the world. These submissions underwent a double-blind peer review process. Of those 568 submissions, 192 submissions (including 14 poster papers) were selected for inclusion in these proceedings. Despite computer science's comparatively brief history as a formal academic discipline, it has made a number of fundamental contributions to science and society-in fact, along with electronics, it is a founding science of the current epoch of human history ('the Information Age') and a main driver of the Information Revolution. The goal of this conference is to provide a platform for researchers to present fundamental contributions, and to be a premier venue for academic and industry practitioners to share new ideas and development experiences. This book collects state of the art chapters on all aspects of Computer Science, from classical to intelligent. It covers both the theory and applications of the latest computer technologies and methodologies. Providing the state of the art in intelligent methods and techniques for solving real-world problems, along with a vision of future research, the book will be interesting and valuable for a broad readership. .
Statistical Learning of Lattice Option Pricing and Traders' Behavior using Ising Spin Model for Asymmetric Information Transitions -- Deep Time Series Neural Networks and Fluorescence Data Stream Noise Detection -- Controlled Under-Sampling with Majority Voting Ensemble Learning for Class Imbalance Problem -- Optimisation of Hadoop MapReduce Configuration Parameter Settings using Genetic Algorithms -- Fast Interpolation and Fourier Transform in High-Dimensional Spaces -- Developing an Asynchronous Technique to Evaluate the Performance of SDN HP Aruba Switch and OVS -- Energy Aware Cluster-Head Selection for Improving Network Life Time in Wireless Sensor Network -- Estimation of Stress Condition of Children by Nasal Skin Temperature -- Private Collaborative Business Benchmarking in the Cloud -- Mobile Phone Operations Just by Sight and its Applications -- Music4D: Audio Solution for Virtual Reality -- Enabling STEAM (Science, Technology, Engineering, Arts, Mathematics) Education with Virtual Reality.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence